Ultrasound Elastography for the Evaluation of Lymph Nodes - Wang, Bin; Guo, Qi; Wang, Jia-Yu; Yu, Yang; Yi, Ai-Jiao; Cui, Xin-Wu; Dietrich, Christoph F. (Frontiers in Oncology, 2021)
The differential diagnosis of lymphadenopathy is important for predicting prognosis, staging, and monitoring the treatment, especially for cancer patients. Conventional computed tomography and magnetic resonance imaging characterize LN with a disappointing sensitivity and specificity. Conventional ultrasound with the advantage of high resolution has widely used for the Lymph node (LN) evaluation. Ultrasound elastography (UE) using colour map or shear wave velocity can noninvasively demonstrate the stiffness and homogeneity of both cortex and medulla of LNs, and detect the early circumscribed malignant infiltration. There is a need of a review to comprehensively discuss the current knowledge of the applications of various UE techniques in the evaluation of LNs. In this review, we discussed the principles of strain elastography and shear wave-based elastography, and their advantages and limitations in the evaluation of LNs. In addition, we comprehensively introduced the applications of various UE techniques in the differential diagnosis of reactive LNs, lymphoma, metastatic LNs and other lymphadenopathy. Moreover, the applications of endoscopic ultrasound elastography and endobronchial ultrasound elastography are also discussed, including their use for improving the positive rate of diagnosis of fine-needle aspiration biopsy.